2011
DOI: 10.1103/physrevlett.106.240504
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Unconditional One-Way Quantum Computations for Continuous Variables

Abstract: One-way quantum computation is a very promising candidate to fulfill the capabilities of quantum information processing. Here we demonstrate an important set of unitary operations for continuous variables using a linear cluster state of four entangled optical modes. These operations are performed in a fully measurement-controlled and completely unconditional fashion. We implement three different levels of squeezing operations and a Fourier transformation, all of which are accessible by selecting the correct qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
140
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 40 publications
(87 reference statements)
3
140
0
Order By: Relevance
“…Successively, a controlled-X gate based on a fourmode optical CV cluster state was presented by Peng's group, in which a pair of quantum teleportation elements were used for the transformation of quantum states from input target and control states to output states [18]. Later, the squeezing operation, Fourier transformation and controlled-phase gate were also achieved by Ukai et al, in which four-mode optical cluster states served as resource quantum states [14,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successively, a controlled-X gate based on a fourmode optical CV cluster state was presented by Peng's group, in which a pair of quantum teleportation elements were used for the transformation of quantum states from input target and control states to output states [18]. Later, the squeezing operation, Fourier transformation and controlled-phase gate were also achieved by Ukai et al, in which four-mode optical cluster states served as resource quantum states [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…1 (b) only by choosing appropriate measurement angles and feedforward circuit. In the one-way quantum computation scheme with the four-mode cluster state as the resource , the excess noises of the amplitude (δ xc ) and phase (δ pc ) quadratures of the output mode for the squeezing of a dB (a < 0 and a > 0 correspond to phase squeezing and amplitude squeezing, respectively) are given by [14] δ xĉ…”
Section: Protocol and Principle Of Quantum Logical Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A N -mode cluster state in CV can be constructed by sending N squeezed modes into a suitably chosen linear optical network [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cluster states, a type of multipartite entangled states, are basic quantum resources for one-way quantum computation [1,2]. Based on a prepared large scale cluster state, one-way quantum computation can be implemented by measurement and feedforward of the measured results [3][4][5][6]. It has been demonstrated that a local quantum network can be built by distributing a multipartite entangled state among quantum nodes [7][8][9][10].…”
mentioning
confidence: 99%